Quantificação de polifenois, taninos e flavonoides na seiva de Jatropha mollissima (Pohl) Baill utilizando espectroscopia no infravermelho e quimiometria - Silva, Tiago dos Santos (2022)
The genus Jatropha belongs to the Euphorbiaceae family and has about 175 species that are widely distributed in tropical and subtropical regions of Africa and the Americas. Jatropha mollissima (Pohl) Baill, popularly known in northeastern Brazil as Pinhão Bravo, is a plant traditionally used in folk medicine for the treatment of several diseases, for its antibacterial, antiphidic, and antioxidant effects, among others. Among the secondary metabolites found in this species are flavonoids, phenols, and tannins, which can vary in concentration depending on variables such as planting location, sap collection season, rainfall rate, among others. The quantification of these substances is usually performed by UV-visible spectroscopy and High Performance Liquid Chromatography (HPLC), however, despite being well known and reliable, they require several steps of sample preparation. The objective of this work was to develop a method based on near and mid infrared spectroscopy (NIR) and chemometric methods for the fast and non-destructive quantification of these metabolites in samples of the sap of the species J. mollissima, collected in 3 different regions of the state of Paraíba. All samples were analyzed by the reference colorimetric method (Uv-vis) and had their NIR and MID spectra recorded. The analyses of the samples by colorimetric methods indicated total tannin contents ranging from approximately 18.4 to 597 µg.mL-1 , total flavonoids ranging from 0.91 to 6.94 µg.mL-1 , and polyphenols content ranging from approximately 0.03 to 55.17 µg.mL-1 . To build the multivariate calibration model, the data sets (NIR and MID) were split into calibration and prediction using the SPXy algorithm. The multivariate calibration models by Partial Least Squares (PLS) were built using the PLS-Toolbox extension of MATLAB. For flavonoids the best model was built with the mid-infrared data (RMSEP=0.75 µg mL-1), whereas for tannin and polyphenols the best models were obtained for NIR data, RMSEP of 54.28 and 5.87 µg mL-1, respectively. All models were built using 7 latent variables and validated by full crossvalidation. No work was found in the literature that performed the quantification of polyphenols, flavonoids and tannins using infrared spectroscopy and multivariate calibration methods for the species J. mollisima. However when compared with PLS models for determination of these metabolites in other natural product samples the errors were comparable.